1990
DOI: 10.1128/iai.58.7.2237-2240.1990
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of calves to Cryptosporidium parvum: effects of age and previous exposure

Abstract: Cryptosporidium parvum is a coccidian parasite that causes diarrheal disease in many vertebrate species, including young (less than or equal to 1 month old) calves. Older calves and adult cattle are resistant to infection. In this study, newborn calves were raised in isolation from C. parvum for 1 week to 3 months before experimental challenge with the parasite. Calves orally challenged with C. parvum at 1 week of age shed oocysts in their feces and had diarrhea after challenge exposure. When these calves were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 20 publications
(27 reference statements)
1
32
0
Order By: Relevance
“…However, diarrhea caused by C parvum rarely occurs after 3 months of age. [57][58][59][60][61][62][63] After infection, clinical signs peak at 3 to 5 days and last 4 to 17 days. 60,64 Some studies have shown that up to 100% of dairy calves become infected with C parvum, 58,65 and become the major source of environmental contamination because calves shed up to 10 7 oocysts per gram of feces.…”
Section: Foster and Smithmentioning
confidence: 99%
See 1 more Smart Citation
“…However, diarrhea caused by C parvum rarely occurs after 3 months of age. [57][58][59][60][61][62][63] After infection, clinical signs peak at 3 to 5 days and last 4 to 17 days. 60,64 Some studies have shown that up to 100% of dairy calves become infected with C parvum, 58,65 and become the major source of environmental contamination because calves shed up to 10 7 oocysts per gram of feces.…”
Section: Foster and Smithmentioning
confidence: 99%
“…59,66 Calves appear to be resistant to subsequent infection after the initial episode of C parvum diarrhea. 63 Severity of diarrhea and incidence of clinical signs in calves shedding oocysts can be variable within and between farms, leading some to question the true importance of C parvum as a primary pathogen; 67 however, it has been repeatedly isolated independent of other known pathogens in clinical cases. 57…”
Section: Foster and Smithmentioning
confidence: 99%
“…Adult beef and dairy cattle also pose little risk with respect to zoonotic transmission of C. parvum as infections are extremely rare. Following infection, calves develop lasting immunity to C. parvum and are resistant to secondary challenge [26]. Thus, the high prevalence of the parasite amongst young dairy calves combined with the development of immunity, probably accounts for the low prevalence of C. parvum in adult dairy cows.…”
Section: Targeting the Actual Reservoirmentioning
confidence: 99%
“…In practice, oocyst excretion has been described as early as 3 days of age, which means that calves are already susceptible for infection during or shortly after birth [37±39]. Calves raised in isolation from Cryptosporidium remain susceptible to infection at older age, but the clinical signs become less severe [40]. In neonates, a great variability was observed in the severity and duration of diarrhoea due to cryptosporidiosis, even when the animals were exposed to similar conditions.…”
Section: Clinical and Pathological Featuresmentioning
confidence: 99%